Scattering Analysis of Rectangular Cavity with Input and Output Waveguides and Its Application to Material Characterization - Nurhafizah, Abu Talip; Kitazawa, Toshihide; Mohamad Shaiful, Abdul Karim (2017)
A method for scattering analysis is proposed to evaluate the resonant characteristics of rectangular cavity with the input and output waveguides including a columnar sample. The analytical method is based on hybrid electromagnetic procedure and affords the efficient and accurate frequency characteristics. The rectangular waveguide cavity is designed optimally by the present method, and the prototype cavity is used to evaluate the complex permittivity of the columnar samples. The virtual and actual measurements confirmed the validity of the evaluation method.